Penanaman Nilai Karakter Keislaman Pada Siswa Kelas V di MIN Batang Bulu - Amar Makruf Rangkuti (Pusat Riset dan Inovasi Nasional, 2024)
The aim of this research is to describe the Islamic character education of fifth grade students in accordance with the nature of development, concepts, evaluation, obstacles and challenges in implementing activities. Data collection through observation, interviews and then analysis. Islamic character-based education is implicitly implemented at MIN Batang Bulu with the learning of Worship. The characters built are; faith and piety, care and empathy, courtesy, patience, obedience and discipline. Then routine evaluations are carried out based on the development of basic competencies and overall character development targets based on children's natural, unique and different nature. The obstacle experienced by schools is the lack of parental cooperation in synergizing habits at home. By developing Islamic character according to students' nature, education becomes easy because Allah has given stages according to interests and characteristics to become a pleasant experience